2016
DOI: 10.1038/srep26913
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Plasmonic Heating on Visible Light Driven Photocatalysis of Gold Nanoparticle Decorated Zinc Oxide Nanorods

Abstract: Herein we explore the role of localized plasmonic heat generated by resonantly excited gold (Au) NPs on visible light driven photocatalysis process. Au NPs are deposited on the surface of vertically aligned zinc oxide nanorods (ZnO NRs). The localized heat generated by Au NPs under 532 nm continuous laser excitation (SPR excitation) was experimentally probed using Raman spectroscopy by following the phonon modes of ZnO. Under the resonant excitation the temperature at the surface of the Au-ZnO NRs reaches up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 43 publications
1
80
0
2
Order By: Relevance
“…Furthermore,arecent study suggested hot-hole transfer as areaction mechanism. [67] This temperature is sufficiently high to overcome the potential barrier, and thus,c hemical reactions are able to proceed. [66] It was reported that, under the excitation of the LSP of Au NPs deposited on zinc oxide nanorods (NRs), the temperature at the surface of the system reached up to approximately 300 8 8C.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Furthermore,arecent study suggested hot-hole transfer as areaction mechanism. [67] This temperature is sufficiently high to overcome the potential barrier, and thus,c hemical reactions are able to proceed. [66] It was reported that, under the excitation of the LSP of Au NPs deposited on zinc oxide nanorods (NRs), the temperature at the surface of the system reached up to approximately 300 8 8C.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Finally, the energy of the LSP is dissipated as heat by thermal conduction, and is used to induce thermal reactions of the molecules (Figure f) . It was reported that, under the excitation of the LSP of Au NPs deposited on zinc oxide nanorods (NRs), the temperature at the surface of the system reached up to approximately 300 °C . This temperature is sufficiently high to overcome the potential barrier, and thus, chemical reactions are able to proceed.…”
Section: Excitation Mechanisms Of Molecules In Plasmon‐induced Chemicmentioning
confidence: 99%
“…Theoretical calculations have predicted a maximum surface heat flux of 150 W m −2 for Au nanospheres ( d =110 nm) with an associated equilibrium temperature of 252 °C . Experimentally, the temperature was detected to increase up to 300 °C for ZnO nanorods with Au nanoparticles ( d =7–23 nm) deposited on the surface under laser excitation (532 nm, 250 W m −2 ) . The heat generated can then be transferred to the surrounding medium by elevation of the local temperature.…”
Section: Figurementioning
confidence: 99%